(untitled) (World Economics and Finance Bulletin, 2024)
In this scientific article, it is highlighted that one of the main problems in the activities of the agricultural farms of the Kashkadarya region of the Republic of Uzbekistan, as well as increasing the level of marketability of products, is the creation and implementation of a system of measures aimed at the timely and high-quality sale of agricultural products grown by them through various channels and obtaining added value. suggestions and recommendations for their solution are given. Also, in addition to the analysis of the level of marketability of the products, in order to evaluate the possibility of creating added value, sales methods, i.e. sales processes of freshly cut, stored for a while and processed, were analyzed